Efeitos do exercício físico regular de natação sobre desenvolvimento e progressão da Encefalomielite Autoimune Experimental (EAE) - Danielle Bernardes (2013)
The experimental autoimmune encephalomyelitis (EAE) is the model to study the Multiple Sclerosis (MS) disease and has been characterized by histopathological hallmarks that include inflammation, demyelination and axonal damage. On the other hand, regular physical exercise is recognized for its anti-inflammatory and neuro-protective effects. Besides, it is suggested that regular exercise can have some protective effect against cachexia, which is a condition associated to the EAE model following the clinical presentation of disease. However, it is not clear if exercise has beneficial effects in central nervous system (CNS) or in systemic metabolic alterations of experimental autoimmune encephalomyelitis (EAE) mice. Therefore, the interactions between a prior program of regular exercise and the development and progression of EAE model were evaluated in the present study. For that, female C57BL/6 mice were assigned in two groups: untrained and exercise-trained. The swimming exercise was realized 5 days a week by 30 minutes a day. After 4 weeks of physical exercise protocol, the peptide MOG35–55 was injected and the animals continued exercising until 10 days post induction, completing 6 weeks of regular exercise. Analyses were made at onset (10 dpi), first peak disease (between 14 and 20 dpi) and at chronic time point of disease (42 dpi) and included: systemic metabolic assessment, intravital microscopy, histopathology (inflammatory infiltrates and demyelination volume), flow cytometry profile of cells, immunohistochemistry for oligodendrocytes (CC1+, NG2+/PDGFRα) and axonal damage (SMI-32+), ELISA (cytokines and brain derived neurotrophic factor – BDNF) and western blot (PLP, MBP and SMI-32). We observed different clinical score from12 to 42 dpi between prior trained and untrained mice (P < 0.0001). Although there was an important attenuation of body weight loss by exercised EAE animals in comparison with the non-exercised ones, the metabolic alterations were not modified. Moreover, in spite of non effect on infiltrated cells, cytokines and BDNF levels were altered in association with clinical score attenuation in exercised EAE-mice. While cytokines were decreased in brain but increased in spinal cord, BDNF was elevated in both compartments in the exercised EAE-group in comparison to the untrained. Also, being physical trained alters specific profile of recruitment of leucocytes (CD4, CD8 and B cells) to the spinal cord and contribute to a lesser demyelization volume and axonal damage at 42 day post induction. These results corroborates the controvert features between neuroinflammation and neuroprotection with singular responses between the two CNS compartments at acute phase of disease. Regular exercise performed before induction acted synergistically with the EAE model and can have some protective effect at chronic time point. However, further studies are necessary to improve the understanding about the molecular outcomes of these synergic effects between prior exercise and pathologic hallmarks of EAE.